2019
DOI: 10.1017/s0022215119001208
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and potential of three-dimensional printing in laryngotracheal stenosis

Abstract: BackgroundThe use of three-dimensional printing has been rapidly expanding over the last several decades. Virtual surgical three-dimensional simulation and planning has been shown to increase efficiency and accuracy in various clinical scenarios.ObjectivesTo report the feasibility of three-dimensional printing in paediatric laryngotracheal stenosis and discuss potential applications of three-dimensional printed models in airway surgery.MethodRetrospective case series in a tertiary care aerodigestive centre.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…Balakrishan et al [ 29 ] reported the impact of 3D printing on surgical planning in a case series of five children who underwent open airway surgery. Richard et al [ 3 ] described the usefulness of preoperatively practicing resection and anastomosis of 3D models of two children with tracheal stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balakrishan et al [ 29 ] reported the impact of 3D printing on surgical planning in a case series of five children who underwent open airway surgery. Richard et al [ 3 ] described the usefulness of preoperatively practicing resection and anastomosis of 3D models of two children with tracheal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) printing is being employed in a variety of surgical specialties to improve patient care and is becoming standard of care in some [1]. These models enable preoperative in vitro planning [2,3], production of tailor-made grafts and stents [4,5], advanced training of surgical residents and improved patient education [6]. In otolaryngology, recent studies reported the use of 3D models of the larynx and trachea for laryngotracheal reconstruction (LTR) rehearsal [7], for training in endoscopic balloon dilations of subglottic stenosis [8], for creating tissue-engineered airway grafts [9,10], and for other procedures [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, 3D imaging and printing technology, known as rapid prototyping, has become a new clinical application, which is widely used in preoperation evaluation or for surgical teaching, 24 but its application for difficult airways is sparse. From this case, we realised that tracheal intubation simulation training with 3D printing for the management of a predictable difficult airway may assist us in saving intubation time and improving the overall success rate.…”
mentioning
confidence: 99%
“…The use of three-dimensional (3D) printing as a tool for virtual surgical 3D simulation and planning has been shown to increase efficiency and accuracy in various clinical scenarios. Richard et al 7 have demonstrated the feasibility of using 3D printing in paediatric laryngotracheal stenosis and described its potential. An earlier study, 8 from Italy, had examined the use of 3D printing in upper airway stenosis in seven patients and found it useful.…”
mentioning
confidence: 99%
“…Richard et al . 7 have demonstrated the feasibility of using 3D printing in paediatric laryngotracheal stenosis and described its potential. An earlier study, 8 from Italy, had examined the use of 3D printing in upper airway stenosis in seven patients and found it useful.…”
mentioning
confidence: 99%